2003
DOI: 10.1002/jcb.10687
|View full text |Cite
|
Sign up to set email alerts
|

Alternative splicing of fibronectin mRNAs in chondrosarcoma cells: Role of far upstream intron sequences

Abstract: The fibronectin (FN) gene encodes multiple mRNAs through the process of alternative splicing, and production of certain isoforms is characteristic of a given cell type. Chondrocytes produce FNs that completely lack alternative exon EIIIA, and loss of inclusion of the exon is tightly linked to chondrogenic condensation of mesenchymal cells. The inclusion of a second exon, EIIIB, is high in embryonic cartilage, but declines with age. Multiple exons are omitted to produce the (V + C)-form that is highly specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
(64 reference statements)
0
6
0
Order By: Relevance
“…In systems of alternative splicing, PTB often serves as a repressor of highly tissuespecific exons outside of a particular cell type, such as muscle cells or neurons (Wagner and Garcia-Blanco 2001;Black and Grabowski 2003). Many mammalian alternative exons are known to be affected by the action of PTB, including exons in actinin (Southby et al 1999;Gromak et al 2003), tropomyosin (Mulligan et al 1992;Gooding et al 1994Gooding et al , 1998Pérez et al 1997a), troponin (Charlet et al 2002), c-src (Chan and Black 1997;Chou et al 2000), fibronectin (Norton 1994;Flanagan et al 2003), FGF receptors 1 and 2 (Carstens et al 2000;Jin et al 2003), and IgM (Shen et al 2004). In all of these transcripts, PTB binds to short pyrimidine-rich elements within the RNA encompassing the regulated exon.…”
Section: Introductionmentioning
confidence: 99%
“…In systems of alternative splicing, PTB often serves as a repressor of highly tissuespecific exons outside of a particular cell type, such as muscle cells or neurons (Wagner and Garcia-Blanco 2001;Black and Grabowski 2003). Many mammalian alternative exons are known to be affected by the action of PTB, including exons in actinin (Southby et al 1999;Gromak et al 2003), tropomyosin (Mulligan et al 1992;Gooding et al 1994Gooding et al , 1998Pérez et al 1997a), troponin (Charlet et al 2002), c-src (Chan and Black 1997;Chou et al 2000), fibronectin (Norton 1994;Flanagan et al 2003), FGF receptors 1 and 2 (Carstens et al 2000;Jin et al 2003), and IgM (Shen et al 2004). In all of these transcripts, PTB binds to short pyrimidine-rich elements within the RNA encompassing the regulated exon.…”
Section: Introductionmentioning
confidence: 99%
“…Our preliminary data also showed that at least two additional minor distal cis elements in intron 9 contributing, respectively, to exon 10 exclusion may exist (data not shown). Although distal intronic cis elements to regulate alternative splicing have been described (Modafferi and Black 1997;Flanagan et al 2003;Li et al 2003), they are usually weak and more difficult to be identified because they are located far from exons and are less accessible to spliceosome and other machineries required for splicing (Graveley et al 1998). We were unable to pinpoint the exact sequences in introns 9 and 10 in this report.…”
Section: Discussionmentioning
confidence: 72%
“…81 In addition, it also plays a significant role in tumor cell microenvironment. 77 The identified contrast expressions among the two studies illustrate a novel detail that, although both OGS and CSA are primary bone tumors that grow at different life stages and mature in various timelines, they regulate differentially in the tumors of both untreated groups. The higher expressions of FN in the OGS-untreated group indicate tumor cell proliferation and differentiation, etc., in the growing bones of children, which should be suppressed by therapy.…”
Section: ■ Discussionmentioning
confidence: 92%
“…Mounting evidence reported that FN is a crucial ECM protein widely distributed and mediates numerous cellular interactions such as cell adhesion, migration, cartilage growth regulation, and differentiation. , It regulates critical mechanisms by interacting with ECM molecules such as collagens, integrins, fibrins, etc., Moreover, FN from young, growing, and adult cartilage suggests regulating the cartilage differentiation in tumors . In addition, it also plays a significant role in tumor cell microenvironment …”
Section: Discussionmentioning
confidence: 99%